Calidad de datos en sistemas de gestión académica universitaria basado en ISO/IEC 25012 - Peralta Ascue, Marleny (2021)
This article proposes a data quality evaluation model developed on the primary basis of the ISO/IEC 25012 standard, applied to a University Academic Management System, to improve data quality. The proposed model is developed from the perspective of the data consumer and the vision of inherent data quality. The sample consisted of the data stored in the Academic Management System of the Universidad Nacional Micaela Bastidas, Apurímac, Perú, with 22 tables, 154 attributes, and 319 685 records. The model begins with data quality requirements as the primary input for its evaluation and ends with an improvement plan, automatically implemented using data cleaning tools and SQL code. The characteristics that affect data quality problems are accuracy, consistency, compliance, and timeliness. Finally, I conclude that it is possible to improve the quality of data by applying the proposed model, which can be used to create and generate value through the exploration, exploitation, and analysis of data for the benefit of university academic management.